Antimicrobial, Antioxidant Properties and Chemical Composition of Some Spices/Herbs - Yavuzdurmaz, Hatice; Baysal, Ayşe Handan (Izmir Institute of Technology, 2013)
The present study aims to investigate the chemical composition, antimicrobial activity, and mechanism of antimicrobial activity, antioxidant properties of essential oils and extracts and the effects of them when applied to minced beef samples. For this purposes; four essential oils (bay leaf, thyme, clove and cumin), two extracts (grape seed and olive leaf) and constituents of essential oils (eucalyptol, linalool, α-terpineol and α-pinene) were subjected to related tests. Chemical characterization was complemented for all essential oils and extracts. Antimicrobial activity was examined against Staphylococcus aureus, Escherichia coli O157:H7, Salmonella Typhimurium, Listeria innocua, Shewanella putrefaciens, Carnobacterium divergens and Serratia liquefaciens. All tested compounds were effective on the bacteria with different concentrations. Antioxidant activity was proved by FRAP and DPPH methods. Physical disturbance and changes in the structures of bacteria was demonstrated by various techniques. The activity of two most potent essential oils (thyme and clove) was investigated in the minced meat application study. The findings represented that clove essential oil restricted the growth of S. Typhimurium and coliform bacteria. They did not have a significant inhibition effect on the aerobic mesophilic bacteria, total yeasts and molds and also psychrotrophic organisms. The results indicated that L* and a* values were maintained during the storage period. The featured effect of essential oils was antioxidant characteristic in meat application study. All treatment showed significant reduction in oxidation comparing with control. The obtained results may suggest that tested essential oils possess compounds with antimicrobial characteristic as well as antioxidant activity and therefore they can be used as natural preservatives in food especially in meat products.
Thesis (Doctoral)--Izmir Institute of Technology, Food Engineering, Izmir, 2013
Includes bibliographical references (leaves: 93-107)
Text in English; Abstract: Turkish an English
xiv, 111 leaves
Keywords: Essences and essential oils--Microbiology; Essences and essential oils--Analysis; Food additives; Anti-infective agents; Antioxidants; Meat--Preservation; Meat--Microbiology